Risk and coping strategies on online shopping of selected UP Diliman students - Calvero, Merril-Krya C.; Amonoy, Mary Justine Clarise A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This study aimed to describe the risks and coping strategies in online shopping of selected students of the University of the Philippines Diliman. It specifically aimed : to describe risk perceptions towards online shopping, determine their actual risk experiences, assess the influences of these risks in their online shopping behavior, and to look at their coping strategies in dealing with their risk experiences. Sixty-four students were samples in the study and were asked to answer the Risk Perception Scale in order to determine their perceived risks in terms of functional, financial and security, time, psychological and social. Twenty--one of the respondents were further selected to participate in the interview on their actual risk experiences and coping strategies. Results showed that a high risk level was obtained across all perceived risks, but the two lowest means came from the psychological and social risks, respectively at 1.90 and 1.95, followed by time risk at 2.10, financial and security risk at 2.31 and functional risk at 2.41 across product categories. In terms of the actual risk experiences , results showed that delivery errors was the most frequent actual experience while seller's inability to handle complaints and dissatisfaction in the product being the least. On buyers' coping strategies , ignoring actual experience and providing feedback to the seller were the two strategies frequently applied. In spite of the risk s and actual experiences faced, 86% of the respondents affirmed their intent to still continue doing online shopping by being keener to understand product features. Through these results , this study hopes to provide further insights as to what process can still be improved on the part of an online seller based on the risks a consumer may face every time an online transaction will be consummated. This study also hopes to help consumers make wise decisions in terms of choosing which shopping environment would satisfy their needs.
Submitted November 2019.
Thesis (B.S. Home Economics)--University of the Philippines Diliman
Keywords: Teleshopping; Risk perception